Corporate Social Responsibility and Sustainability (CSRS) Initiatives among European and Asian Business Schools: A Web-based Content Analysis. Issue 5 (October 2019) - Rehman, Mohsin Abdur; Kashif, Muhammad; Mingione, Michela
The purpose of this study is to explore the extent to which MBA programmes offered by top European and Asian B-schools have a corporate social responsibility and sustainability (CSRS) orientation as per their websites. The websites of top-200 (based on the QS Global Business and Management University Rankings 2015) European and Asian B-schools were explored and content analysed to reach meaningful conclusions. The findings reveal European B-schools have much stronger CSRS orientation once compared with the Asian B-schools. Furthermore, only few B-schools promote CSRS centres on their websites which has some useful practical implications. This is the first study to explore the CSRS orientation among top-200 European and Asian B-schools based on an analysis of their respective websites. Additionally, a cross-continental comparison between European and Asian MBA programmes is unique to this study. The results have implications for global managers, in general, and business school policymakers, in specific, to embark the CSR initiatives to gain competitive advantage.